2019
DOI: 10.1155/2019/2492590
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis in Fetal Skeletal Dysplasias by Trio Whole-Exome Sequencing

Abstract: Skeletal dysplasias (SDs) comprise a series of severe congenital disorders that have strong clinical heterogeneity and usually attribute to diverse genetic variations. The pathogenesis of more than half of SDs remains unclear. Additionally, the clinical manifestations of fetal SDs are ambiguous, which poses a big challenge for accurate diagnosis. In this study, eight unrelated families with fetal SD were recruited and subjected to sequential tests including chromosomal karyotyping, chromosomal microarray analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
3
39
1
Order By: Relevance
“…Due to the strong clinical and genetic heterogeneities, searching for the causative mutations of skeletal dysplasia remains a task with big challenges. With the advance of next-generation sequencing (NGS) technology, attempts have been made to implement and apply it to offer a comprehensive strategy in clinical practice (Liu et al, 2019;Yang et al, 2019). In the current study, through integration of WES and molecular analyses, we identified novel pathogenic compound mutations in patients affected with OI: a splicing error-causing mutation (NM_006371.4:c.1153-3C > G) and a large deletion in the CRTAP gene (hg19, chr3:g.32398837_34210906del).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strong clinical and genetic heterogeneities, searching for the causative mutations of skeletal dysplasia remains a task with big challenges. With the advance of next-generation sequencing (NGS) technology, attempts have been made to implement and apply it to offer a comprehensive strategy in clinical practice (Liu et al, 2019;Yang et al, 2019). In the current study, through integration of WES and molecular analyses, we identified novel pathogenic compound mutations in patients affected with OI: a splicing error-causing mutation (NM_006371.4:c.1153-3C > G) and a large deletion in the CRTAP gene (hg19, chr3:g.32398837_34210906del).…”
Section: Discussionmentioning
confidence: 99%
“…After induced abortion, more DNA was extracted from umbilical cord sample and then used for WES detection. DNA fragments hybridization (by IDT’s xGen Exome Research Panel, Integrated DNA Technologies), library quality testing, and WES sequencing (using Novaseq6000 platform, Illumina) were performed as described in our previous study . Sanger sequencing was used to verify the variation of suspected pathogenicity.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA samples were extracted from chorionic villi, amniocytes, fetal tissues or parental blood using a Qiagen DNA Blood Midi/Mini kit (Qiagen GmbH, Hilden, Germany) following the manufacturer's protocol. Then WES was performed according to the published paper 5 . And data was analyzed on the Cruxome system developed by Berry Genomics.…”
Section: Whole Exome Sequencingmentioning
confidence: 99%